Efficacy of psychotherapy for anxiety reduction in hospital management of women successfully treated for preterm labor: a randomized controlled trial. Issue 10 (25th November 2020) - Mirtabar, Seyyedeh Mahboubeh; Faramarzi, Mahbobeh; Khazaei, Razieh; Dini, Mohammadreza
ABSTRACT: Preterm labor (PTL) is associated with high anxiety and stress in pregnant women. The study investigated the effect of adding psychotherapy to hospital management of pregnant women with successfully treated for PTLon improving anxiety, pregnancy stress, and perceived control. In a randomized controlled trial study, sixty pregnant women with gestational ages of 24 to 37 weeks and successfully treated forPTL were randomly divided into the experimental (n = 30) and control group (n = 30). The experimental group received psychotherapy along with medical care in individual face-to-facesessions, 1 h per day for 6 consecutive days.The control group received medical care for PTL. Objective outcomes were assessed via the State-Anxiety Inventory, Prenatal Distress Questionnaire (NuPDQ), and Perceived Pregnancy Control at pre-trial and post-trial. The results revealed that psychotherapy significantly improved mean pregnancy distress (45.80 ± 2.29 vs. 43.80 ± 1.93), state anxiety (47.46 ± 5.92 vs. 41.60 ± 5.46), and perceived control (2.86 ± 1.59 vs. 5.26 ± 1.38) in women with PTL from beginning to end of the intervention. The findings suggest that adding psychotherapy to hospital management of women successfully treated for PTLcan be considered a potential method to reduce anxiety and pregnancy-specific stress.